COMMUNITY PARTICIPATION IN THE TREE PLANTING AND MAINTENANCE MOVEMENT PROGRAM IN ENVIRONMENTAL MANAGEMENT - Rozan, Zahra Syifa (JURNAL SOCIUS, 2025)
The purpose of this study was to identify community participation in the tree planting and maintenance movement program for environmental management in Mugarsari Village, Tamansari District, Tasikmalaya City, Forestry Service Branch Region VI. This study uses a qualitative method. In this study, the subjects of this study were the Head of CDK Region VI, Head of the GTPP Program, Head of Community Groups and the community who participated in the tree planting and maintenance movement program on critical land of the Forestry Service Branch Region VI, especially Mugarsari Village, Tamansari District, Tasikmalaya City. Data collection techniques in this study were observation, interviews and documentation. Data analysis techniques in this study were carried out in several stages, namely, data reduction, data presentation and drawing conclusions. The results of the GTPP program research have had a positive impact on the community in Mugarsari Village, CDK Region VI, by increasing community authority, independence, and cooperation between parties. The program has also had a positive impact on the environment and the community's economy.